Drosophila glob1 is required for the maintenance of cytoskeletal integrity during oogenesis. - Yadav, R.; Sarkar, S. (Developmental Dynamics, 2016)
Hemoglobins (Hbs) are evolutionarily conserved heme-containing metallo-proteins of the Globin protein family that harbour the characteristic "globin fold." Hemoglobins have been functionally diversified during evolution and their usual property of oxygen transport is rather a recent adaptation. Drosophila genome possesses three globin genes (glob1, glob2, and glob3), and we have reported earlier that adequate expression of glob1 is required for various aspects of development, as well as to regulate the cellular level of reactive oxygen species (ROS). The present study illustrates the explicit role of Drosophila globin1 in progression of oogenesis. We demonstrate a dynamic expression pattern of glob1 in somatic and germ cell derivatives of developing egg chambers during various stages of oogenesis, which largely confines around the F-actin-rich cellular components. Reduced expression of glob1 leads to various types of abnormalities during oogenesis, which were primarily mediated by the inappropriately formed F-actin-based cytoskeleton. Our subsequent analysis in the somatic and germ line clones shows cell autonomous role of glob1 in the maintenance of the integrity of F-actin-based cytoskeleton components in the somatic and germ cell derivatives. Our study establishes a novel role of glob1 in maintenance of F-actin-based cytoskeleton during progression of oogenesis in Drosophila. Developmental Dynamics 245:1048-1065, 2016. © 2016 Wiley Periodicals, Inc.